Studies of The Influence of Factors on Life Expectancy ("Journal "U". Economy. Management. Finance.", 2021)
This article examines the life expectancy of the population for the period 2005-2020. We will analyze the influence of various factors and its dynamics. Calculate the average growth rate and check the multicollinearity of the factors. It is revealed that it affects life expectancy.
Keywords: life expectancy; socio-economic phenomenon; pair regression; health status; mortality rate